2014
DOI: 10.1080/03043797.2014.895701
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of the professional competencies required in engineering asset management

Abstract: Engineering asset management (EAM) is a rapidly growing and developing field. However, efforts to select and develop engineers in this area are complicated by our lack of understanding of the full range of competencies required to perform. This exploratory study sought to clarify and categorise the professional competencies required of individuals at different hierarchical levels within EAM. Data from 14 field interviews, 61 online surveys, and 10 expert panel interviews were used to develop an initial profess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Research exploring the promotion and understanding of intrapersonal competencies within engineering education has included effort beliefs (e.g., Snyder et al, 2018), incremental beliefs about intelligence (e.g., Stump et al, 2014), self‐regulated learning (e.g., Nelson et al, 2015), reflection (e.g., Turns et al, 2014), metacognition (e.g., Cunningham et al, 2015), emotional intelligence (Elegbe, 2015; Skipper & Brandenburg, 2013), emotional resilience (Jesiek et al, 2014), adaptability (Ahn et al, 2012), emotional awareness (Bish et al, 2014), working under pressure (Walther et al, 2011), empathy (Hess, Strobel, Pan, & Wachter Morris, 2016; Walther, Miller, & Sochacka, 2017), and mindfulness (Goldberg & Somerville, 2014). The sum of this literature suggests that possessing these intrapersonal competencies supports positive outcomes within an engineering context.…”
Section: Introductionmentioning
confidence: 99%
“…Research exploring the promotion and understanding of intrapersonal competencies within engineering education has included effort beliefs (e.g., Snyder et al, 2018), incremental beliefs about intelligence (e.g., Stump et al, 2014), self‐regulated learning (e.g., Nelson et al, 2015), reflection (e.g., Turns et al, 2014), metacognition (e.g., Cunningham et al, 2015), emotional intelligence (Elegbe, 2015; Skipper & Brandenburg, 2013), emotional resilience (Jesiek et al, 2014), adaptability (Ahn et al, 2012), emotional awareness (Bish et al, 2014), working under pressure (Walther et al, 2011), empathy (Hess, Strobel, Pan, & Wachter Morris, 2016; Walther, Miller, & Sochacka, 2017), and mindfulness (Goldberg & Somerville, 2014). The sum of this literature suggests that possessing these intrapersonal competencies supports positive outcomes within an engineering context.…”
Section: Introductionmentioning
confidence: 99%
“…Then again, a study by Mansur (2018) found that leadership commitment significantly influences the quality of financial statements and has a significant effect through physical asset optimization. Yet, in their study, Bish et al (2014) discovered that Engineers need to be able to collaborate and influence others, complete objectives within organizational guidelines and be able to manage competency clusters effectively for success to be registered. A study by Al Hassan et al (2013) concluded on two fronts.…”
Section: Authentic Leadership and Physical Asset Management Practicesmentioning
confidence: 99%
“…ESI competencies have been found to predict outstanding leader, manager, or professional performance across a variety of professions (Boyatzis, 2009; Druskat et al , 2005) and have been proposed as important to engineers’ capability (Passow, 2012; Lappalainen, 2015; Lopes et al , 2015; Bish et al , 2014). Synthesizing the literature, the competencies appear in three clusters: cognitive intelligence competencies, such as systems thinking or pattern recognition; emotional intelligence competencies, such as adaptability, emotional self-control, emotional self-awareness, positive outlook, and achievement orientation; and Social intelligence competencies, such as empathy, organizational awareness, inspirational leadership, influence, coaching and mentoring, conflict management (i.e.…”
Section: Esi Relationships and Engineer Effectivenessmentioning
confidence: 99%